2007
DOI: 10.1177/0038038507082320
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gender Equality and Democracy: A Comparison of Arab Versus Non-Arab Muslim Societies

Abstract: Inglehart and Norris argue that the core clash between the Islamic world and the West is over issues concerning gender equality rather than democracy. However, a comparison between Arab and non-Arab Muslim societies is essential before drawing this conclusion. Here, we compared nations from each society and found significant differences in attitudes toward gender equality, democratic governance and religious identities. We analyzed models predicting support for democracy including views toward gender equality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(115 citation statements)
references
References 36 publications
3
92
1
4
Order By: Relevance
“…Macro forces influence religious beliefs and practices, gender beliefs and practices, and other attitudes and behaviors in important ways (Adamczyk and Hayes 2012;Adamczyk and Pitt 2009;Charles 2011;Gerhards et al 2009;Rizzo et al 2007;Stavrova et al 2013). State-level research in the United States has shown that the more religious fundamentalism in a state, the more conservative the individual gender attitudes of people who live in that state, even apart from the individual's own religiosity (Moore and Vanneman 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Macro forces influence religious beliefs and practices, gender beliefs and practices, and other attitudes and behaviors in important ways (Adamczyk and Hayes 2012;Adamczyk and Pitt 2009;Charles 2011;Gerhards et al 2009;Rizzo et al 2007;Stavrova et al 2013). State-level research in the United States has shown that the more religious fundamentalism in a state, the more conservative the individual gender attitudes of people who live in that state, even apart from the individual's own religiosity (Moore and Vanneman 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with these findings, however, other empirical studies have found that although Muslims strongly support democratic political values and institutions, they maintain patriarchal social values (Alexander and Welzel 2011;Norris and Inglehart 2002;Rizzo et al 2007). Norris and Inglehart used World Values Survey items to compare support for political and social values in Islamic majority countries against western/non-Muslim majority nations.…”
Section: Introductionmentioning
confidence: 73%
“…These three questions have previously been used and validated as a scale to measure support for patriarchy among Muslim populations by Alexander and Welzel (2011). Both Rizzo et al (2007) and Asadullah and Chaudhury (2010) have also employed variations on these questions to measure support for patriarchy among Muslim populations. The three WVS questions on gender equality had different response scales, and were thus recoded into a uniform scale for consistency (0-1.0), using the same method employed by Alexander and Welzel (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic gender inequalities which are common across the Arab region were attributed to Islamic teaching and deeply entrenched Urf (societal norms) particularly patriarchal kinship patterns, social subordination and ingrained male dominance (e.g., Abdalla 1996;Kauser & Tlaiss, 2011;Rizzo, Abdel-Latif & Meyer, 2007;UNDP, 2005;Wilkinson, 1996). While researchers agree on the adverse role of Urf on women's economic and political participation, there is partial disagreement on the exact role of Islamic religion in impeding women careers.…”
Section: Review Of Literature On the Arab Worldmentioning
confidence: 99%